Pengaruh Beban Kerja dan Kompensasi Terhadap Kepuasan Kerja dan Turnover Intention Karyawan - Hammam Zaki; Marzolina Marzolina (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2018)
The purpose of this study was to determine the effect of workload and compensation for job satisfaction and turnover intention of employees at PT. Adira Quantum Multifianance Pekanbaru branch. The research sample as many as 157 people were selected using census method that is the entire population being sampled, while data collected using questionnaires and analysis techniques used are two-stage regression analysis using SPSS version 22.The results showed that the workload significantly affect job satisfaction, and compensation have a significant impact on job satisfaction, workload and compensation simultaneously significant effect on job satisfaction and job satisfaction significantly influence employee turnover intention. The results of this study is, any increase job satisfaction hence potentially lower workload, and high compensation potential to increase job satisfaction. Increased job satisfaction has the potential to reduce the rate of employee turnover intention. Keywords :workload, compensation, job statisfaction, tunrnover intention